(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Student-centered instruction has become a crucial approach in secondary education, emphasizing the distinct needs, interests, and learning styles of students. This article examines the foundational principles of student-centered learning, its advantages, effective strategies for implementation, and the challenges educators may encounter. By nurturing an engaging and collaborative atmosphere, student-centered instruction not only boosts academic performance but also develops essential life skills in students.